1965
DOI: 10.1152/jappl.1965.20.3.480
|View full text |Cite
|
Sign up to set email alerts
|

Lung volume for initiation of phonation

Abstract: The percent of vital capacity at which phonation is normally initiated was investigated. Thirty normal young male and thirty normal young female adults breathed oxygen in a closed circuit respirometer in a standing position. Vital capacity, expiratory reserve, tidal volume for breathing, and phonation volume were determined for each subject. The mean percent of vital capacity at which phonation is normally initiated was found to be 49.7 for males and 50.3 for females. These values approximate end-inspiratory v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…and 16.8% for the deaf group. These values agree satisfactorily with 17.5% reported by Hoshiko [1965] and 13.2% by Hoshiko and Blockcolsky [1967] for their normal male subjects. The Mann-Whitncy U test [Siegel, 1956] percent of VC between the normal-hearing and deaf groups.…”
Section: Respiratory Characteristics Associated With Quiet Breathing supporting
confidence: 89%
“…and 16.8% for the deaf group. These values agree satisfactorily with 17.5% reported by Hoshiko [1965] and 13.2% by Hoshiko and Blockcolsky [1967] for their normal male subjects. The Mann-Whitncy U test [Siegel, 1956] percent of VC between the normal-hearing and deaf groups.…”
Section: Respiratory Characteristics Associated With Quiet Breathing supporting
confidence: 89%
“…• Normal speech. The equation for ER q in (13) needs to be modified in a similar way as (15), replacing the droplet volume concentration C d with the value for normal speech in (14) and we take as tidal volume the value V T = 600 cm 3 , roughly 10 % larger than the average rest value [118,119]. To incorporate the timing we replace N (vp) with a number count of breaths coinciding with a given percentage of an hour interval spent on continuously speaking in a given indoor environmant.…”
Section: Infective Quantamentioning
confidence: 99%
“…As mentioned in section 3, higher powered devices associated with DTL vaping tend to increase ECA droplet sizes and diameters [26, 22] but it is not certain if this applies to respiratory droplets. However, as mentioned in section 7, speech involves droplet generating mechanisms that are distinct from those of breathing [91, 84, 82], resulting in higher rate of droplet emission even with a tidal volume only slightly larger than the breathing rest value of 400 − 600 cm 3 [114, 115]. Thus, we have two plausible options to account for a higher total volume of exhaled droplets 𝒱 d = V T 𝒞 d : it may follow simply from a larger V T with the same value 𝒞 d = 3 × 10 −3 mL / m 3 of low intensity vaping, or we might assume the larger value of C d for normal speech in (12).…”
Section: A Simplified Risk Modelmentioning
confidence: 99%
“…The breath requirements for speech production are not quite different from those required for life purposes. Approximately 50 percent of vital capacity is inhaled for speech purposes, it concludes that if the breathing behaviour of the individual is within normal broad limits and is sufficiently deep for life purposes, it ought to be perfectly adequate for speech purposes [2]. By comparing children's and adult's respiratory behaviour during speech task found that, at loud intensity, adults used a higher percentage of their vital capacity than the children [3].…”
Section: Introducrtionmentioning
confidence: 99%